The Relationship Between Physical Function and Psychological Symptoms in Parkinson's: A Survey of UK-Based Physiotherapists: Psychophysical Interactions in Parkinson's Disease - Hodgson, Philip; Sinani, Dr Charikleia; Jordan, Dr Alastair; Charura, Professor Divine (Journal of Physiotherapy in Mental Health, 2025)
Objectives: People with Parkinson’s Disease (PwP) often experience both motor and non-motor symptoms, including psychological symptoms such as anxiety and depression. However, the relationship between these symptoms and the perspectives of physiotherapists are not well understood. This study describes current approaches to physiotherapy assessment and onward referrals for psychological symptoms. We explore the views of physiotherapists based in the United Kingdom (UK) around the potential interaction between physical function and psychological symptoms in PwP. Design: Cross-sectional using an anonymous online survey, ensuring confidentiality and voluntary participation. Data are reported as descriptive statistics. Participants: UK-based physiotherapists recruited by convenience and purposive sampling. Results: 125 UK-based physiotherapists completed the survey, with questions focusing on their work with PwP, mental health training/experience, outcome measures used, symptom interactions, treatments, and onward referrals. Most reported extensive clinical experience and greater use of outcome measures to assess physical function than psychological symptoms. Whilst altered physical function was often reported to be recognised before psychological symptoms, a direct link between the two was widely acknowledged, notably including symptoms of anxiety and depression. Barriers to onward referrals for psychological symptoms were commonly reported. Conclusions: UK-based physiotherapists recognise a relationship between physical function and psychological symptoms in Parkinson's. However, psychological symptoms are under-assessed in clinical practice, and barriers to onward referral exist. Efforts should be made to improve assessment of psychological symptoms by physiotherapists and address barriers to onward referrals. Enhancing physiotherapists assessment of psychological symptoms and overcoming barriers to onward referrals is essential to provide comprehensive care for PwP.